ANALISIS BANDINGAN UNSUR INTRINSIK LEGENDA “ASAL-USUL DANAU TOBA” dan MUKASHI BANASHI “TSURU NO HANASHI” - Oktavia,, lukiana wati; Muzakka, Mohamad (Japanese Literature, 2015)
Oktavia, Lukiana Wati. 2015. Intrinsic Elements Analysis of Folktales "The Legend of Toba Lake" and Mukashi Banashi “Tsuru no Hanashi” (Comparative Study of Literature). Thesis of Japanese Department, First supervisor: Drs. Moh. Muzakka, M. Hum. Second supervisor: Yuliani Rahmah, S.Pd, M.Hum. Folktales are folk proses that every country has. All folktales, including Japanese ones, have universal story types and motives. They can be analysed based on their intrinsic elements. Analysis of intrinsic elements is structural analysis involving point of views, flow (plot), characters and characterizations, background (setting) and themes. After analysing those intrinsic elements, comparative study of literature is applied to identify the similarities and differences between both folktales. Comparative study of literature is a literature study beyond state boundaries and study of the correlation between literature and other disciplines and beliefs, such as art (e.g. painting, sculpture, music), ideology, history, social science (e.g. politics, economy, sociology), natural science and religion. The folktales analysed by the researcher are "The Legend of Toba Lake" from Batak, North Sumatra and Mukashi Banashi "Tsuru no Hanashi" from Japan. The result shows that there are similarities in the themes, characters and characterizations, flows (plot) and point of views. Moreover, the differences come from the characters and characterizations. The folktales analysed by the researcher are "The Legend of Toba Lake" from Batak, North Sumatra and Mukashi Banashi "Tsuru no Hanashi" from Japan. The result shows that there are sim have universal story types and motives. They can be analysed based on their intrinsic elements. Analysis of intrinsic elements is structural analysis involving point of views, flow (plot), characters and characterizations, background (setting) and themes. After analysing those intrinsic elements, comparative study of literature is applied to identify the similarities and differences between both folktales. Comparative study of literature is a literature study beyond state boundaries and study of the correlation between literature and other disciplines and beliefs, such as art (e.g. painting, sculpture, music), ideology, history, social science (e.g. politics, economy, sociology), natural science and religion. The folktales analysed by the researcher are "The Legend of Toba Lake" from Batak, North Sumatra and Mukashi Banashi "Tsuru no Hanashi" from Japan. The result shows that there are similarities in the themes, characters and characterizations, flows (plot) and point of views. Moreover, the differences come from the characters and characterizations. The folktales analysed by the researcher are "The Legend of Toba Lake" from Batak, North Sumatra and Mukashi Banashi "Tsuru no Hanashi" from Japan. The result shows that there are similarities in the themes, characters and characterizations, flows (plot) and point of views. Moreover, the differences come from the characters and characterizations.